Perancangan Sistem Penjadwalan Dan Pengontrolan Produksi Perusahaan Padupadan - Marsheilla Marsheilla; Marsheilly Marsheilly (Universitas Kristen Maranatha, 2019)
The development of garment industry, especially for export, may bring certain challenges to Micro Small and Medium Enterprises (MSME). The company that export its products has to handle its production carefully, in particular for the export deadline. When the company fail to deliver its products on time, a high amount of fine, approximately 30% of total production cost, will be faced. Padupadan is a garment focusing on local product. To be competitive, it needs to improve its quality in both scheduling and production control. Orders has been accepted without actual information status of running order which cause delay and low product quality. Due to that situation, this company needs a system that assist decision making relating to controlling orders and performance of any parties in production process.Case study was used as method of this explanatory research. Data were analyzed using MIT 90’s Framework and Data Flow Diagram. Design of Padupadan production system is related with 9 analyzed activities, namely marketing, sales order, production scheduling, human resource management, purchasing, receiving, warehouse (raw material), production, and warehouse (finished goods) which will be structured and standardized for the company. This system provides assistance in determining production scheduling target, system to control production that will help owner in evaluating employees, performance of production department and categorized supplier. Owner provides positive respon on the design since it can assist the company for future advance. Keywords: Scheduling System Control; Production Control